EFEKTIVITAS PENDIDIKAN KESEHATAN MELALUI AUDIO VISUAL TENTANG BULLYING TERHADAP PENGETAHUAN DAN SIKAP SISWA SMP NEGERI 38 PEKANBARU - Irma Fransiska; Riski Novera Yenita; Rika Mianna (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2020)
Bullying is aggressive behavior and deliberate acts of violence by a person or group of people repeatedly and from time to time in the form of hurting others verbally, physically, psychologically and on social media so that the victim cannot defend himself which results in the victim being bullied become depressed, traumatized and helpless. Bullying cases currently do not only occur in the community, but have also penetrated the world of education, one of which is in schools. This study aims to analyze the effectiveness of health education through audio visuals about bullying on the knowledge and attitudes of students at SMP Negeri 38 Pekanbaru. This study used a quasi experimental method using a pretest-posttest control group design. The number of samples in this study were 21 respondents each in the experimental group and the control group. Retrieval of data using a research questionnaire. Data were analyzed using the T-Independent test. The results showed that audio-visual media about bullying was effective (p = 0.000) on the level of knowledge and attitudes between groups, but not effective between treatments. The conclusion of this study is that audio-visual media is effective between groups but not effective between treatments for knowledge and attitudes about bullying. It is hoped that the results of this study will become information material for schools to provide more information about bullying